Membrane-based technologies for meeting the recovery of biologically active compounds from foods and their by-products - Castro-Muñoz, Roberto; Conidi, Carmela; Cassano, Alfredo (Critical reviews in food science and nutrition, 2019)
To date, according to the latest literature inputs, membranes-based technologies (microfiltration, ultrafiltration and nanofiltration) have demonstrated to meet the recovery of biologically active compounds, mainly phenolic compounds and their derivatives, from agro-food products and by-products. The goal of this paper is to provide a critical overview of the on ongoing development works aimed at improving the separation, fractionation and concentration of phenolic compounds and their derivatives from their original sources. The literature data are analyzed and discussed in relation to separation processes, molecule properties, membrane characteristics and key factors affecting the performance of such technologies. Technological advances and improvements over conventional technologies, as well as critical aspects to be further investigated are highlighted and discussed. Finally, a critical outlook about the current status for a large-scale application and the role of these processes from an environmental viewpoint is provided.
Keywords: ultrafiltrace; Phenolic compounds; Phenols; membrány umělé; potravinářská technologie; agro-food by-products; nanofiltration; chemická frakcionace; Ultrafiltration; Food Analysis; Chemical Fractionation; ultrafiltration; analýza potravin; fenoly; Membranes, Artificial; foods; Food Technology